Electoral geography. theoretical approaches for the argentinian case (2009)
This paper focuses in electoral geography, a subdiscipline of politic geography that approaches the vote from a space-time perspective of electoral results in order to respond to the search for causes that explain these results. Although electoral geography emerged as a result of the quantitative paradigm (applying techniques from Geographic Information Systems, given its character of space-time study and of multi criteria analysis), this paper embraces both qualitative and quantitative factors by relating electoral results and sociodemographic features of the studied population in Argentina. This work also proposes an analysis on the process before, during and after election day. It intends to be a contribution to academic environments of this subdiscipline and those concerned about citizenship and civic activity of the society, essential in the Latin American context.